47.2k views
5 votes
Use the following for questions 1 - 6.f(x) = 2x - 3g(x) = 6x2 - 7x - 3h(x) = x3 – 2x2 + 3x - 5==1. f(x) – g(x)2. g(x) + h(x)

Use the following for questions 1 - 6.f(x) = 2x - 3g(x) = 6x2 - 7x - 3h(x) = x3 – 2x-example-1

1 Answer

2 votes

\begin{gathered} f(x)=2x-3 \\ g(x)=6x^2-7x-3 \end{gathered}

To subtract g(x) from f(x), we simply have to plug in the given values of the function written above.


\begin{gathered} =f(x)-g(x) \\ =(2x-3)-(6x^2-7x-3) \end{gathered}

Then, solve.

First, eliminate the parenthesis by distributing the symbol/number outside of it to the numbers inside the parenthesis.


=2x-3-6x^2+7x+3

Next, combine similar terms. We have 2x + 7x and -3 + 3.


=9x-6x^2

Lastly, arrange the terms according to highest degree (highest exponent).


=-6x^2+9x

Hence, f(x) - g(x) = -6x² + 9x.

User LastElb
by
4.8k points